2004
DOI: 10.1121/1.1785672
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variations in the whistles of spinner dolphins (Stenella longirostris) of the Main Hawai‵ian Islands

Abstract: Geographic variations in the whistles of Hawai'ian spinner dolphins are discussed by comparing 27 spinner dolphin pods recorded in waters off the Islands of Kaua'i, O'ahu, Lana'i, and Hawai'i. Three different behavioral states, the number of dolphins observed in each pod, and ten parameters extracted from each whistle contour were considered by using clustering and discriminant function analyses. The results suggest that spinner dolphin pods in the Main Hawai'ian Islands share characteristics in approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…It is also known that spinner dolphin whistles can vary geographically ͑Bazúa- Durán and Au, 2001;Bazúa-Durán et al, 2003;Bazúa-Durán and Au, 2004͒, as it was already observed for bottlenose dolphins, Tursiops truncatus ͑Wang et al, 1995b;Jones and Sayigh, 2002͒, and for the estuarine dolphin, Sotalia guianensis ͑Azevedo and Van Sluys, 2005͒. Nevertheless, the factors influencing this observed geographic variation are still unclear, once the pattern found for spinner dolphins does not follow exactly those observed for the other two species.…”
Section: Introductionmentioning
confidence: 79%
“…It is also known that spinner dolphin whistles can vary geographically ͑Bazúa- Durán and Au, 2001;Bazúa-Durán et al, 2003;Bazúa-Durán and Au, 2004͒, as it was already observed for bottlenose dolphins, Tursiops truncatus ͑Wang et al, 1995b;Jones and Sayigh, 2002͒, and for the estuarine dolphin, Sotalia guianensis ͑Azevedo and Van Sluys, 2005͒. Nevertheless, the factors influencing this observed geographic variation are still unclear, once the pattern found for spinner dolphins does not follow exactly those observed for the other two species.…”
Section: Introductionmentioning
confidence: 79%
“…g. Herzing, 1996;Van Parijs et al, 2000;Bazúa-Durán and Au, 2004͒ and they seem to be related to whistle functions, which include to transmit emotional states and to coordinate dolphin activities ͑Tyack, 1998͒. Whistles produced by Atlantic spotted dolphins varied among the two behavioral states in which dolphins were engaged.…”
Section: Discussionmentioning
confidence: 98%
“…These signals have been the focus of several bioacoustic studies on delphinids due to the numerous easily measured characteristics presented by them. In addition, they have been used for characterization and comparisons among groups and populations ͑e.g., Rendell et al, 1999;Bazúa-Durán and Au, 2004;Azevedo and Van Sluys, 2005;May-Collado and Wartzok, 2009͒. Atlantic spotted dolphins ͑Stenella frontalis͒ are found in warm temperate to tropical waters in Atlantic Ocean ͑Jef-ferson et al, 2008͒. As most delphinids, this species is a highly vocal dolphin species that produces echolocation click trains, burst pulse sounds, and whistles related to behavioral activities ͑Perrin, 2002͒.…”
Section: Introductionmentioning
confidence: 98%
“…These three frequency measurements are standard in Guyana dolphin whistle studies ͑see Azevedo and Van Sluys, 2005;Erber and Simão, 2004;Rossi-Santos and Podos, 2006͒. Peak frequency ͑PF͒ was also measured and is defined as the frequency at which maximum power occurs ͑Bazúa-Durán and Au, , 2004May-Collado and Wartzok, 2007͒ and number of harmonics ͑e.g., Wang et al, 1995;Erber and Simão, 2004͒. Whistle contours were categorized as ascending, descending, ascending-descending, descending-ascending, and constant in frequency, sine, and others ͑see Azevedo and Van Sluys, 2005; Erber and Simão, 2004͒.…”
Section: B Whistle Recordings and Analysismentioning
confidence: 99%
“…Seven standard whistle variables were measured on the fundamental frequency of each: starting frequency ͑SF͒, ending frequency ͑EF͒, minimum frequency ͑MinF͒, maximum frequency ͑MaxF͒, delta frequency ͑DF= MaxF− MinF͒, duration ͑s͒, and number of inflection points ͑see, e.g., Wang et al, 1995;Oswald et al, 2003Oswald et al, , 2004Erber and Simão 2004; Bazúa-Durán and Au, , 2004Azevedo and Van Sluys, 2005;Baron et al, 2008͒. In addition, the contour was divided into four parts equally distributed in time to measure the frequency at 1 4 , 1 2 , and 3 4 of the contour. These three frequency measurements are standard in Guyana dolphin whistle studies ͑see Azevedo and Van Sluys, 2005;Erber and Simão, 2004;Rossi-Santos and Podos, 2006͒.…”
Section: B Whistle Recordings and Analysismentioning
confidence: 99%